Practical history lessons as a tool for generating procedural knowledge in history teaching (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
Situated in the context of philosophy of history, this article explains the use of substantive concepts and procedural concepts to generate historical understanding and examines the relationship between the two forms of historical knowledge. The paper makes use of both primary (original views of authors) and secondary (views of other authors) materials. The paper notes that substantive knowledge and procedural knowledge play complementary roles in the acquisition of historical understanding. It is argued, in light of the dominant position of substantive knowledge over procedural knowledge, that aention should be given to procedural knowledge as it introduces students to the processes by which history is constructed. The article proposes the use of practical history lessons as a conduit for developing procedural knowledge and attaining historical understanding.
Keywords: History; History curriculum; Philosophy of history; Practical history lessons; Procedural knowledge; substantive knowledge; Teaching of history